Corporate Social Responsability – an European Approach through the Tourism SME’s Perspectives - Gabriela Ţigu; Delia Popescu; Remus Ion Hornoiu (Amfiteatru Economic)
Nowadays, companies face a big challenge in adopting a responsible behaviour towards the community and the environment throughout their business activities. We consider that Corporate Social Responsibility in tourism industry is still searching for consist ency in policies, programs and practices and responds to issues particularly related to sustainable tourism principles. Starting from the idea that small and medium sized enterprises can be exponents of responsibility, this paper propose to analyse tourism operators’ opinions regarding Corporate Social Responsibility and underlines its importance in tourism businesses. For achieving this, a quantitative research was used and a questionnaire on the micro, small and medium sized enterprises, representatives for tourism industry in eight EU countries (United Kingdom, Germany, Austria, Belgium, Lithuania, Latvia, Romania and France) was conducted. The tour operators’ opinions on CSR are significant for the development of trainings that they might attend in order to implement the social responsibility principles in their fields of activity.